Do Pentavalent (DTwP-Hib-HBV) vaccines have sex-differential nonspecific effects? An observational study - Thomas Aamand; Ane Bærent Fisker; Claudino Correia; Manuel Fernandes; Clara Clipet-Jensen; Sanne Marie Thysen (Human Vaccines & Immunotherapeutics)
Vaccines may alter the ability to combat infections unrelated to the target disease, i.e. have “nonspecific effects.” The non-live Diphtheria-Tetanus-Pertussis vaccine (DTP) has been associated with increased child mortality, especially for females. In 2008, the DTP-containing Pentavalent vaccine replaced DTP vaccine in Guinea-Bissau. We investigate female relative to male mortality after Penta vaccination. In Guinea-Bissau, Bandim Health Project (BHP) registered children’s vaccination and vital status at biannual village visits and provided vaccines. Among children Penta-vaccinated by BHP, we compared mortality of males and females in Cox proportional hazards models. Children aged 6 weeks to 8 months entered the analysis at the date of vaccination and were followed for up to 6 months. Between September 2008 and December 2017, 33,989 children aged 6 weeks to 8 months were under surveillance. Of these 12,753 (females: 6,363; males: 6,390) received Penta by the BHP and entered the study contributing with 19,667 observations. The mortality rate following Penta vaccination was 25.2 per 1,000 person years for females and 26.6 for males, resulting in an adjusted Female/Male mortality rate ratio of (F/M aMRR) 1.01 (0.82–1.25). The association between sex and mortality differed by timeliness of vaccination, F/M aMRR: 0.62 (0.41–0.93) for children vaccinated below median age, and F/M aMRR: 1.38 (0.90–2.13) for children vaccinated above median age. We did not find higher overall mortality in females than males after Penta vaccination. Our findings suggest that mortality differences between males and females following Penta vaccination may depend on timeliness of Penta vaccination.